We will discuss here about some of the problems on quadratic equations.

**1. Solve: x^2 = 36**

x^2 = 36

or, x^2 - 36=0

or, (x + 6)(x - 6) = 0

So, one of x + 6 and x - 6 must be zero

From x + 6 = 0, we get x = -6

From x - 6 = 0, we get x = 6

Thus, the required solutions are x = ± 6

Keeping the expression involving the unknown quantity and the constant term on left and right side respectively and finding square root from both sides, we can solve the equation also.

As in the equation x^2 = 36, finding square root from both sides, we get x = ± 6.

**2. Solve 2x^2 - 5x + 3 = 0**

2x^2 - 5x + 3 = 0

or 2x^2 - 3x – 2x + 3=0

or, x (2x - 3) - 1 (2x - 3)=0

or, (x - 1)(2x - 3) = 0

Therefore, one of (x - 1) and (2x - 3) must be zero.

when, x - 1 = 0, x = 1

and when 2x - 3 = 0, x = 3/2

Thus required solutions are x = 1, 3/2

**3. Solve: ****3x^2 - x = 10**

3x^2 - x = 10

or, 3x^2 - x - 10 = 0

or, 3x^2 - 6x + 5x - 10 = 0

or, 3x (x - 2) + 5 (x - 2) =0

or, (x - 2)(3x + 5) = 0

Therefore, one of x - 2 and 3x + 5 must be zero

When x - 2 = 0, x = 2

and when 3x + 5 = 0; 3x = -5 or; x = -5/3

Therefore, required solutions are x= -5/3, 2

**4. Solve: (x - 7)(x - 9) = 195**

(x - 7)(x - 9) = 195

or, x^2 - 9x – 7x + 63 – 195 = O

or, x2 - 16x - 132=0

or, x^2 - 22 x + 6x - 132=0

or, x(x - 22) + 6(x - 22) = 0

or, (x - 22)(x + 6) = 0

Therefore, one of x - 22 and x + 6 must be zero.

When x - 22, x = 22

when x + 6 = 0, x = - 6

Required solutions are x= -6, 22

**5. Solve: x/3 +3/x = 4 1/4**

or, x^{2} + 9/3x = 17/4

or, 4x^{2} + 36 = 51x

or, 4x^2 - 51x + 36 = 0

or, 4x^2 - 48x - 3x + 36 = 0

or, 4x(x- 12) -3(x - 12) = 0

or, (x - 12)(4x -3) = 0

Therefore, one of (x - 12) and (4x - 3) must be zero.

When x - 12 = 0, x = 12 when 4x -3 = 0,x = 3/4

**6. Solve: x - 3/x + 3 - x + 3/x - 3 + 6 6/7 = 0**

Assuming x - 3/x + 3 = a, the given equation can be written as:

a - 1/a + 6 6/7 = 0

or, a^{2} - 1/a + 48/7 = 0

or, a^{2} - 1/a = - 48/7

or, 7a^2 - 7 = - 48a

or, 7a^2 + 48a - 7 = 0

or,7a^2 + 49a - a - 7 = 0

or, 7a(a + 7) - 1 (a + 7) = 0

or,(a + 7)(7a - 1) = 0

Therefore, 0ne of (a + 7) and (7a - 1) must be zero.

a + 7 = 0 gives a = -7 and 7a - 1 = 0 gives a = 1/7

From a = -7 we get x -3/x + 3 = -7

or, x – 3 = -7x - 2 1

or, 8x = -18

Therefore, x = -18/8 = - 9/4

Again, from a = 1/7, we get x - 3/x + 3 = 1/ 7

or, 7x - 21 = x + 3

or,6x = 24

Therefore, x = 4

Required solutions are x = -9/4, 4

**Quadratic Equation**

**Introduction to Quadratic Equation**

**Formation of Quadratic Equation in One Variable**

**General Properties of Quadratic Equation**

**Methods of Solving Quadratic Equations**

**Examine the Roots of a Quadratic Equation**

**Problems on Quadratic Equations**

**Quadratic Equations by Factoring**

**Word Problems Using Quadratic Formula**

**Examples on Quadratic Equations **

**Word Problems on Quadratic Equations by Factoring**

**Worksheet on Formation of Quadratic Equation in One Variable**

**Worksheet on Quadratic Formula**

**Worksheet on Nature of the Roots of a Quadratic Equation**

**Worksheet on Word Problems on Quadratic Equations by Factoring**

**From Problems on Quadratic Equations to HOME PAGE**

**Didn't find what you were looking for? Or want to know more information
about Math Only Math.
Use this Google Search to find what you need.**

## New! Comments

Have your say about what you just read! Leave me a comment in the box below. Ask a Question or Answer a Question.